Pengaruh Penerapan Tata Tertib Terhadap Kedisiplinan Peserta Didik di SMK Bina Pangudi Luhur Jakarta - Azizah, Evi Nur; Firdaus, Firdaus; Ulfah, Maria (Juwara: Jurnal Wawasan dan Aksara, 2024)
This research is motivated by the fact that students' indiscipline in following school rules often becomes a problem, especially at the secondary school level, when students grow up and begin to learn to recognize their identity through imitation or self-imitation. To overcome this problem, sanctions are imposed. The purpose of imposing sanctions is to provide a deterrent effect to students who violate the rules to anticipate repetition of rule violations by students. The research method in this study is the "descriptive analytical correlational" method. X and XI SMK Bina Pangudi Luhur Jakarta. The population in this study was 104 students, and the sample was 82 students. The research method technique uses simple random sampling, to analyze data with product moment correlation (rxy) and hypothesis testing (t test. The results of the research show that the application of regulations has a fairly strong or high correlation, namely 0.40 – 0.50. This It can be proven from the results of testing the hypothesis that the application of rules and regulations has a positive and significant influence on the discipline of students in classes 10 and 11 of Bina Pangudi Luhur Vocational School, Jakarta, namely the calculated t value is 0.450 > 1,990 or positive with a significance level of 0.000 < 0.05, which means that The hypothesis in this study rejects H0 and accepts Ha.